2012
DOI: 10.1051/0004-6361/201219540
|View full text |Cite
|
Sign up to set email alerts
|

Red supergiants around the obscured open cluster Stephenson 2

Abstract: Context. Several clusters of red supergiants have been discovered in a small region of the Milky Way close to the base of the ScutumCrux Arm and the tip of the Long Bar. Population synthesis models indicate that they must be very massive to harbour so many supergiants. Amongst these clusters, Stephenson 2, with a core grouping of 26 red supergiants, is a strong candidate to be the most massive young cluster in the Galaxy. Aims. Stephenson 2 is located close to a region where a strong over-density of red superg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 64 publications
3
56
0
Order By: Relevance
“…Different criteria have been proposed depending on the available resolution. The spectral classification of low-resolution spectra is described in Ginestet et al (1994), Negueruela et al (2011Negueruela et al ( , 2012, and Massey (1998), who presented a classification of RSGs in M 31 and M 33. However, the resolution of our spectra is not high enough to identify luminosity-sensitive features (Fe, Ti) apart from the Ca II triplet, which we used for identifying RSGs in our sample.…”
Section: Spectral Classificationmentioning
confidence: 99%
“…Different criteria have been proposed depending on the available resolution. The spectral classification of low-resolution spectra is described in Ginestet et al (1994), Negueruela et al (2011Negueruela et al ( , 2012, and Massey (1998), who presented a classification of RSGs in M 31 and M 33. However, the resolution of our spectra is not high enough to identify luminosity-sensitive features (Fe, Ti) apart from the Ca II triplet, which we used for identifying RSGs in our sample.…”
Section: Spectral Classificationmentioning
confidence: 99%
“…These clusters are separated from the center of G25.8700+0.1350 by 39 ′ 8 and 22 ′ 6 respectively. Moreover, the largest concentration of red supergiants (RSGs) known in our Galaxy (Negueruela et al 2012;Dorda et al 2016) can be found around these clusters. According to the high density of RSGs, this region probably is one of the most intense star-forming places in the Galaxy.…”
Section: Introductionmentioning
confidence: 81%
“…Due to their high luminosity and low temperature, RSGs appear very bright in the infrared, and thus are easily observable at very large distances, even if they are affected by high extinction. Thanks to this, in the past few years, several massive and highly reddened clusters have been discovered in the inner Galaxy (for example Davies et al 2007;Negueruela et al 2012), in the region where the tip of the Galactic bar is believed to touch the base of the Scutum arm, revealing recent widespread massive star formation in this part of the Milky Way.…”
Section: Introductionmentioning
confidence: 90%
“…Even the CaT becomes unable to separate clearly LC I from LC II and LC III (Negueruela et al 2011). However, the classification is still roughly possible if the spectral type (SpT) is known, as this will predict the TiO bandhead depths, and therefore warn about the erosion suffered by other spectral features (Negueruela et al 2011(Negueruela et al , 2012.…”
Section: Arxiv:160904063v1 [Astro-phsr] 13 Sep 2016mentioning
confidence: 99%
See 1 more Smart Citation